Rekonstruksi Tafsir dalam Anwar Al-Tanzil terhadap Al-Kasyaf: Analisis Komparatif Strategi Tahdzib Al-Baidhawi - Nurul Hidayah Baharuddin; Andi Abdul Hamzah; Mohammad Harjum (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This study comparatively examines the exegetical methodologies of Tafsir al-Kasyaf by al-Zamakhsyari and Anwar al-Tanzil wa Asrar al-Ta’wil by al-Baidhawi, while proposing a conceptual model of the methodological reconstruction employed by al-Baidhawi in responding to his predecessor’s interpretation. This library research employs a qualitative comparative-hermeneutical approach: the comparative dimension is operationalized through six indicators (linguistic structure, argumentation, use of transmitted reports, theological orientation, ta’wil technique, and use of hadith), while the philosophical-hermeneutical dimension draws on Palmer’s (1969) framework to read the methodological intent behind each exegete’s redactional choices. Primary data were drawn from the two classical commentaries; secondary data came from relevant literature on exegesis, Islamic theology, and scholarly articles. This study proposes a new conceptual model—built inductively from close reading rather than adopted as a fixed classical term—describing al-Baidhawi’s tahdzib strategy through three patterns: hadzaf (elimination), talwin (redactional modification), and ta’kid (theological reinforcement). The findings show that Tafsir al-Kasyaf is characterized by a rational-linguistic approach grounded in Mu’tazilite theology, while Anwar al-Tanzil integrates al-Zamakhsyari’s linguistic sophistication with Ash’arite theological principles and a more proportional use of transmitted reports. The relationship between the two works is not mere textual reproduction but a systematic process of tahdzib. As an exploratory model still grounded in two verses, these findings should be tested on a broader corpus of mutashabihat verses, yet they already indicate that Anwar al-Tanzil represents a methodological transformation enriching the classical Sunni exegetical tradition.